2017
DOI: 10.1158/1078-0432.ccr-16-2703
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Lymphoma Patient-Derived Xenograft Models Enable Drug Discovery and Are a Platform for Personalized Therapy

Abstract: Purpose Patients with B-cell lymphomas often relapse after frontline therapy, and novel therapies are urgently needed to provide long-term remission. We established B-cell lymphoma PDX (patient-derived xenograft) models to assess their ability to mimic tumor biology and to identify B-cell lymphoma patient treatment options. Experimental Design We established the PDX models from 16 patients with diffuse large B-cell lymphoma, mantle cell lymphoma, follicular lymphoma, marginal zone lymphoma, or Burkitt’s lymp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…The MCL patient-derived xenograft (PDX) model was established as described previously. 33 All experimental protocols were approved by the Institutional Animal Care and Use Committee of the MD Anderson Cancer Center and performed in accordance with the Declaration of Helsinki. In essence, 6-to 8-week-old male NSG mice (Jackson Laboratory) were housed and monitored in the animal research facility.…”
Section: Pdx Modelmentioning
confidence: 99%
“…The MCL patient-derived xenograft (PDX) model was established as described previously. 33 All experimental protocols were approved by the Institutional Animal Care and Use Committee of the MD Anderson Cancer Center and performed in accordance with the Declaration of Helsinki. In essence, 6-to 8-week-old male NSG mice (Jackson Laboratory) were housed and monitored in the animal research facility.…”
Section: Pdx Modelmentioning
confidence: 99%
“…28 A previous study indicated the importance of PI3K signaling in the development of ibrutinib resistance in a patientderived xenograft model but a possible mechanism was not proposed. 29 A recent report of mantle cell lymphoma demonstrated that inhibition of the PI3K-alpha isoform in the tumor microenvironment overcame ibrutinib resistance. 30 Because pan-PI3K inhibitors might induce off-target cellular toxicity, we elected to examine the effects of various pharmacological inhibitors of PI3K with different isoform inhibition profiles.…”
Section: Simultaneous Inhibition Of Pi3k-beta and Delta Isoforms Sensmentioning
confidence: 99%
“…Six-to 8-week-old female NOD SCID IL2Rg null (NSG) mice (The Jackson Laboratory) were used to create the PDX models, and all experimental procedures and protocols were approved by The University of Texas MD Anderson Institute Animal Care Committee. As described previously (25), fresh human fetal bones of 17 to 19 gestational weeks (Advanced Bioscience Resources) were subcutaneously implanted into (PT 2) SCID or NSG mice (SCID-hu or NSG-hu). Approximately 4 to 6 weeks following implantation, one injection of 5 Â 10 6 freshly isolated tumor cells from MCL or DLBCL patient samples were administered directly into the human fetal bone implants within the SCID-hu NSG-hu hosts.…”
Section: In Vivo Venetoclax Treatment In Pdx Modelsmentioning
confidence: 99%